Pengembangan Lembar Kerja Siswa Berbasis Kontekstual pada Materi Menulis Teks Persuasi Kelas VIII SMP Ar-Risalah Lubuklinggau - Rika Saputri; Satinem Satinem; Sri Murti (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
Student worksheets (LKS) especially in writing persuasion text material used by teachers are still oriented to the text so students have difficulty understanding the material contextually. For this reason, this study aims to develop worksheets for writing contextual persuasion texts based on students of Class VIII at SMP Ar-Risalah Lubuklinggau. This research is a type of Research and Development (R&D) research using the Dick & Carey model. Data collection techniques using interview techniques, questionnaires, and tests. Data analysis techniques for effectiveness testing using SPSS version 20. The results of the study show that LKS writes contextual persuasion text based on Students of Class VIII at SMP Ar-Risalah Lubuklinggau which are developed valid, practical, and effective so that it is appropriate to be used by Indonesian language teachers as one of the teaching materials to achieve the objectives learning to write persuasive texts. Then, the results of the product effectiveness test showed that the use of LKS writing contextual persuasion text writing was able to improve students' persuasion writing skills.